THE INFLUENCE OF DIGITAL TRANSFORMATION ON COMPANY VALUE (CASE STUDY OF DIGITAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018-2023) - Indra Salfian Annur; Harjum Muharam (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of digital transformation on the value of digital bank companies measured using Tobin's Q by considering various financial factors such as profitability level (EPS), liquidity (Current Ratio), leverage (DER), dividend policy (DPR), and company size (total assets) in line with the increase and decrease in financial performance and stock prices of digital banks in Indonesia. The research method uses secondary data obtained from the annual reports of digital banks listed on the Indonesia Stock Exchange during the period 2018 to 2023 and data analysis using multiple linear regression with EViews software. The results of the study show that digital transformation, leverage (DER), company size (Total Assets) have a significant effect on company value, conversely, profitability level (EPS), liquidity (CR) and dividend policy (DPR) do not show a significant effect on company value. This study concludes that digital transformation, leverage, and company size remain determinants in influencing the value of digital bank companies. These findings provide insights for digital banking companies to continue to focus on digital transformation as a primary strategy in increasing competitiveness and company value, as well as providing recommendations for investors to be selective in choosing banks with a healthy capital structure and optimal asset management.